Aristotle and the Ontology of St. Bonaventure - van Buren, Franziska (Ancient and Medieval Philosophy - Series 1, 2023)
Bonaventure's metaphysical thought and his interpretation of Aristotle Contemporary scholarship on Bonaventure has characterized him as the Neo-platonic foil to the Aristotelianism of his day. The present book, however, shows a Bonaventure who is highly enthusiastic about utilizing the philosophy of Aristotle and who centers much of his philosophical project around interpreting and understanding the texts of Aristotle. Two goals are central to this book. The first is to shed light on Bonaventure's greatly understudied ontology and theory of forms, demonstrating how his philosophical system is an important and unique alternative to other medieval Aristotelian systems. The second is to establish, more broadly, how Bonaventure's interpretation of Aristotle is a resource which should be mined for contemporary efforts in thinking about and reading Aristotle himself. Ebook available in Open Access. This publication is GPRC-labeled (Guaranteed Peer-Reviewed Content).